Performing Tao with martial arts and a gentleman with one skill——Cultural positioning and dissemination of Taijiquan from the perspective of Six Arts - Gao, Peng (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Taijiquan is a treasure of Chinese culture. In 2020, Taijiquan has been listed in the list of representative works of world intangible cultural heritage, which ushers in a new historical opportunity for the development of Taijiquan. But at the same time, we should also see that in recent years, Taijiquan is being questioned and denied unprecedentedly-individual Taijiquan practitioners are easily defeated by freestyle fighter, some famous Taijiquan practitioners are suspected of public fraud, and the misunderstanding of Taijiquan in society and academia is getting deeper and deeper. How to find the correct cultural orientation and development orientation, clarify the misunderstanding, grasp the opportunity, and let Taijiquan regain the recognition and respect of the world, is a common topic in front of Taijiquan inheritors, practitioners, researchers and promoters. As we all know, Taijiquan integrates Chinese philosophy, Taoist culture, art of war strategy, fighting and combat, health preservation of traditional Chinese medicine, sports competition and artistic aesthetics, which is extremely rare among all Chinese cultural carriers. This is not only the communication advantage of Taijiquan, but also the communication disadvantage of Taijiquan. If we can not find the correct cultural positioning, it will be difficult for Taijiquan communication to achieve the effect of "integration". Based on this, this paper will explore the deep relationship between Taijiquan and Chinese culture, and seek a more accurate cultural positioning and development positioning for Taijiquan in combination with the classical "Six Arts". Methods: This paper aims to explore the deep relationship between Taijiquan and Chinese culture, combined with the classical "Six Arts" to seek more accurate cultural positioning and development positioning for Taijiquan. The first chapter analyzes the similarities and differences of communication modes between Taijiquan and other traditional skills (to be compared with Calligraphy, Traditional Chinese Medicine and Crosstalk), fitness skills (to be compared with Yoga, Aerobics and Running), and fighting skills (to be compared with Taekwondo, Modern Sanda and Wing-Chun Boxing) from the aspects of cultural heritage, inheritance difficulty, communication mode, communication audience and competitive environment. Through comparison, it can be found that the spread of Taijiquan presents the characteristics of minority, privatization and experience, and its communication advantage mainly lies in the "cultural heritage" - its internal consistency with Chinese culture and Chinese spirit. The second chapter further analyzes the characteristics and shortcomings of the existing Taijiquan cultural positioning. At present, at the discourse level, there are not a few who explain the theory and culture of Taijiquan through the Book of Changes, Taoist thought and Cheng Zhu’s theory. In this way, although the theory of Taijiquan is further Philosophized and metaphysical, it is often too abstruse; at the practical level, in order to popularize and popularize, many Taijiquan routines and practices have been continuously simplified, gradually losing the functions of internal skill cultivation and fighting, and becoming a kind of fitness exercise suitable for all ages. Such a "communication gap" of "one deep and one shallow" has actually created the stereotype of "pretending to be profound" and "not worthy of the name" of Taijiquan for many people. Therefore, it is particularly important to re "match" a set of cultural interpretation discourse for Taijiquan, surpass the binary opposition between tradition and modernity, religion and secular, health preservation and martial arts, and seek the recognition of the majority. In this way, no matter which path to spread Taijiquan along cultural promotion, fighting and fitness, it can be more "justified". The third chapter introduces the "Six Arts" theory to seek a new cultural interpretation and cultural orientation for Taijiquan. the current "Thirteen powers" Taijiquan originated from Zhang Sanfeng, the founder of Wudang school, and belongs to Taoist culture. However, the thought and concept of Taijiquan is not unique to Taoism—As a new form of Confucianism in Song Dynasty, Neo Confucianism has a very deep interpretation of Taiji philosophy. The origin of Taoism (and later Taoism as a religion) and Confucianism can be traced back to the "study of kings and officials" in the Zhou Dynasty. "Six arts" are six kinds of skills under the academic system of the Zhou Dynasty officials, and later passed on and developed into six kinds of skills of the classical scholar class by Confucius. After the Han Dynasty only respected Confucianism, the Confucian "Six Classics" were also called "six arts". This "New Six Arts" not only refers to the classics, but also refers to the value system behind the classics. Therefore, the knowledge system of "Six Arts" including "Old Six Arts" and "New Six Arts" actually covers the "Tao" of China, which integrates scriptures, skills and values. Ma Yifu, a great Confucian in modern times, argues that "Six Arts dominate all academic studies". "Six arts" include "the way of Wushu", "the virtue of Wushu", "Archery" and "driving", which are inseparable from ancient wars. In the past, scholars often took Taijiquan as a way of "performing Tao with martial arts" from the perspective of Taoism, that is, deduce the generation and evolution of the universe and human body through martial arts ; In this paper, I use the perspective of "six arts" to explain "developing Tao with martial arts", that is, the way for a gentleman to improve his self-cultivation through martial arts. Under the general trend of the revival of traditional culture, Taijiquan can fully attract people’s attention and return to the middle and high-end public in the form of "gentleman’s art". Results: The fourth chapter then leads to the new positioning of Taijiquan cultural communication. As a "national art" and "national skill", Taijiquan is a great creation of "performing Taoism with martial arts". Its rich philosophy, culture and elegance are not possessed by other boxing, which is also the fundamental reason why Taijiquan can be carried forward. In order to adapt to the lifestyle of modern society and the revival of traditional culture, Taijiquan should be built into a "gentleman’s art" in modern society. The specific positioning includes three aspects: Taijiquan as the convergence medium of Chinese philosophy, Taijiquan as the presentation means of ritual and music culture, and Taijiquan as a modern elegant lifestyle. It not only inherits Chinese classical culture, but also meets the needs of modern society, and can attract the support of elite public. Conclusion: This paper holds that in the face of public misunderstanding and doubt, Taijiquan should seek a new cultural orientation and communication orientation, that is, when interpreting the cultural value of Taijiquan, we should not only highlight its fitness and fighting, but also bring it into the "six arts" system, highlight its irreplaceable cultural value, return to the public vision with a new image, take advantage of the revival of traditional culture and the popularity of Chinese culture.